New aspects upon the classification of Staphylococcus intermedins - PETRIDOU (Ε. ΠΕΤΡΙΔΟΥ) E.; FARMAKI (Ρ. ΦΑΡΜΑΚΗ) R.; KOUTINAS (Α.Φ. ΚΟΥΤΙΝΑΣ) A. F. (Journal of the Hellenic Veterinary Medical Society, 2017)
In 1976, Staphylococcus intermedins was first described as being a new species isolated from pigeons, dogs, mink and horses. Until recently, the majority of coagulase-positive staphylococci originating from animals such as dogs and pigeons have been classified as S. intermedins. This species has been recognized to constitute normal skin flora of various animal species and to occasionally cause a variety of infections in dogs and cats. There have been six species of coagulase-positive staphylococci other than Staphylococcus aureus, namely S.intermedius, S.schleiferì subsp. coagulans, S.hyicus, S. lutrae, S.delphini and S. pseudintermedius. Sequence similarities of 16S rRNA genes among four of these species, except S. hyicus and S. lutrae, are 99% identical. In addition, it is very difficult to differentiate among S. intermedius, S. delphini and S. pseudintermedius phenotypically, and commercial kits are not available for the differentiation between of S. pseudintermedius and S. delphini. It has been shown that isolates phenotypically identified as Staphylococcus intermedius consist of four distinct species, including S. intermedius, Staphylococcus pseudintermedius and Staphylococcus delphini group A and B, which together represent the Staphylococcus intermedius group (SIG). Moreover, S. delphini group Β might be a novel species. In 2009, a new, rapid and inexpensive PCR-RFLP was developed and is capable of discriminating the SIG strains.